Role of PhyR and growth phase-dependent regulation in Rhodobacter sphaeroides - Li, Qingfeng; Justus Liebig University Giessen (My University, 2019)
The data obtained in this present work demonstrated that PhyR has no major role in the general stress response of the alphaproteobacterium R. sphaeroides, in contrast to other bacteria. We could attribute a role for PhyR in response to membrane stress and UV stress in the dark rather than in oxidative stress in R. sphaeroides, supporting a more specialized function in this bacterium. PhyR has no major contribution to the complex regulatory network (Billenkamp F, et al., 2015, Cabiscol E, et al., 2000, Glaeser J, et al., 2011, Hess WR, et al., 2014) of protein and sRNA regulators that control the oxidative stress response in R. sphaeroides.PhyR was found to have a function in cell viability in the stationary phase. In addition, the activity of three gene promoters (RSP_0557, sitA (RSP_0904) and ccR (RSP_0960)) was determined throughout the growth phase and outgrowth. These genes were selected on the basis of differential regulation as determined by microarray and RNAseq approaches. Transcriptional fusions were constructed between these promoters (genes RSP_0557, sitA (RSP_0904) and ccR (RSP_0960)) and the lacZ reporter system. The three promoters showed growth phase-dependent regulation. The sigma factors RpoHI and RpoHII are clearly important for the overall activity of the RSP_0557 promoter and the sitA promoter under microaerobic growth conditions. However, while RpoHI and RpoHII have a function on the activity of the RSP_0557 promoter in the stationary phase and following outgrowth, they have no function on the growth phase-dependent regulation of sitA under microaerobic growth conditions. Oxygen saturation also has an important role on the regulation of RSP_0557, sitA (RSP_0904) and ccR (RSP_0960) throughout the growth phase. The supercoiling activity of gyrase was also investigated throughout the growth phase. In the wild type strain, after 60h of growth, the cells almost completely lost supercoiling activity, but this was recovered as soon as nutrients became available. Furthermore, it was demonstrated that H-NS and IhfB had an influence on the supercoiling activity of gyrase in the late stationary phase and following outgrowth.
Keywords: ddc:570